MIRAS HUKUKUNUN DEVELOPMENT PROCESS Changes in Socio-Economic Policy in Coca-Cola and Laws and Their Effects on the Development of Inheritance Law - Serozan, Rona; Paksoy, Meliha Sermin (Istanbul Univ, Fac Law, 2015)
[Abstract Not Available]